How Drug Shortages Affect Clinical Care: The Case of the Surgical Anesthetic Propofol. Issue 9 (October 2015) - Romito, Bryan; Stone, Jonathan; Ning, Ning; Yin, Chen; Llano, Ernesto M.; Liu, Jing; Somanath, Keerthan; Lee, Christopher T.; Matchett, Gerald
Background: Periodic drug shortages have become a reality in clinical practice. In 2010, in the context of a nationwide drug shortage, our hospital experienced an abrupt 3-month shortage of the surgical anesthetic propofol. The purpose of this retrospective study was to survey the clinical impact of the abrupt propofol shortage at our hospital and to survey for any change in perioperative mortality. Methods: A retrospective before-and-after analysis, comparing May through July 2010 (group A, prior to the propofol shortage) to August through October 2010 (group B, during the propofol shortage). Results: In May through July 2010, before the propofol shortage, a majority of patients (80%) received propofol (group A, n = 2, 830). In August through October 2010, during the propofol shortage, a majority of patients (81%) received etomidate (group B, n = 3, 066). We observed that net usage of etomidate increased by more than 600% in our hospital. Baseline health characteristics and type of surgery were similar between groups A and B. Thirty-day and 2-year mortality were similar between groups A and B. The reported causes and frequency of mortality in groups A and B were also similar. Conclusion: The propofol shortage led to an increased usage of etomidate by more than 600%. In spite of that, we did not detect an increase in mortality associated with the increased use of etomidate during a 3-month propofol shortage.